SARS-CoV-2 and the Missing Link of Intermediate Hosts in Viral Emergence - What We Can Learn From Other Betacoronaviruses - Schindell, Brayden G.; Allardice, Meagan; McBride, Jessica A.M.; Dennehy, Brendan; Kindrachuk, Jason (Frontiers in Virology, 2022)
The emergence of SARS-CoV-2 in 2019 has resulted in a global pandemic with devastating human health and economic consequences. The development of multiple vaccines, antivirals and supportive care modalities have aided in our efforts to gain control of the pandemic. However, the emergence of multiple variants of concern and spillover into numerous nonhuman animal species could protract the pandemic. Further, these events also increase the difficulty in simultaneously monitoring viral evolution across multiple species and predicting future spillback potential into the human population. Here, we provide historic context regarding the roles of reservoir and intermediate hosts in coronavirus circulation and discuss current knowledge of these for SARS-CoV-2. Increased understanding of SARS-CoV-2 zoonoses are fundamental for efforts to control the global health and economic impacts of COVID-19.